Is visual processing in the dorsal stream accessible to consciousness? - Milner, A. D (Proceedings of the Royal Society. B, Biological sciences, 2012)
There are two highly interconnected clusters of visually responsive areas in the primate cortex. These two clusters have relatively few interconnections with each other, though those interconnections are undoubtedly important. One of the two main clusters (the dorsal stream) links the primary visual cortex (V1) to superior regions of the occipito-parietal cortex, while the other (the ventral stream) links V1 to inferior regions of the occipito-temporal cortex. According to our current understanding of the functional anatomy of these two systems, the dorsal stream's principal role is to provide real-time ‘bottom-up’ visual guidance of our movements online. In contrast, the ventral stream, in conjunction with top-down information from visual and semantic memory, provides perceptual representations that can serve recognition, visual thought, planning and memory offline. In recent years, this interpretation, initially based chiefly on studies of non-human primates and human neurological patients, has been well supported by functional MRI studies in humans. This perspective presents empirical evidence for the contention that the dorsal stream governs the visual control of movement without the intervention of visual awareness.